The Relationship of Physical Activity to Cardiorespiration Endurance in Children Aged 10-12 Years - Kadek Nadinda Putri Wiandani; Indah Pramita; Agung Wahyu Permadi (Universitas Majalengka, 2023)
Cardiorespiratory endurance is a measure of the functional ability of the heart and lungs to supply oxygen in the blood throughout the body. Physical activity affects cardiorespiratory endurance related to increased lung function by increasing forced expiratory volume in 1 second, forced vital capacity and lung volume. The purpose of this study was to determine the relationship between physical activity and cardiorespiratory endurance in children aged 10-12 years. This study uses a cross sectional correlation research method with a sample of 40 people. Measurement of physical activity using PAQ-C, while the measurement of cardiorespiratory endurance using the KPR Test. The results of the Pearson product moment correlation test (p=0.000, r=-0.730) showed a negative correlation between physical activity and cardiorespiratory endurance. The conclusion of this study is that there is a relationship between physical activity and cardiorespiratory endurance in children aged 10-12 years.